2020
DOI: 10.1021/acs.chemrestox.9b00368
|View full text |Cite
|
Sign up to set email alerts
|

Surface Functionalization of Pegylated Gold Nanoparticles with Antioxidants Suppresses Nanoparticle-Induced Oxidative Stress and Neurotoxicity

Abstract: Because of their biocompatibility and biosafety, pegylated Au NPs (Au@PEG), as a nanodrug-carrier, have been widely applied in different biomedical applications, including imaging and drug delivery systems. Under such conditions, the biosafety of Au@PEG has attracted tremendous attention. However, only a small number of studies focused on the neurotoxicity of Au@PEG used as drug delivery carriers not to mention reducing the neurotoxicity of Au@PEG. To address this issue, the adverse effects of Au@PEG on human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 71 publications
(124 reference statements)
1
22
0
Order By: Relevance
“…Their concentrations in cellular organelles are strongly regulated by various detoxifying enzymes, such as superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase (CAT), or by different antioxidants including flavonoids, ascorbic acids, vitamin E, and glutathione (GSH). The production of free radicals induced by nanoparticles leads to a reduction of GSH to oxidized form, followed by induction of oxidative stress [ 2 , 12 , 72 , 73 , 74 , 75 ].…”
Section: Nanoparticle Toxicitymentioning
confidence: 99%
See 3 more Smart Citations
“…Their concentrations in cellular organelles are strongly regulated by various detoxifying enzymes, such as superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase (CAT), or by different antioxidants including flavonoids, ascorbic acids, vitamin E, and glutathione (GSH). The production of free radicals induced by nanoparticles leads to a reduction of GSH to oxidized form, followed by induction of oxidative stress [ 2 , 12 , 72 , 73 , 74 , 75 ].…”
Section: Nanoparticle Toxicitymentioning
confidence: 99%
“…Application of AuPEG at 25 mg/kg for three months caused a decrease in MDA and antioxidant enzyme levels (SOD, CAT, GSH-Px) in the hippocampus, compared to AuTrolox [ 72 ].…”
Section: Nanoparticle Toxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the intracellular response of GNPs still needs further study. Previous studies have shown that GNPs can cause mitochondrial membrane destruction and cell content loss, which is related to the production of reactive oxygen species (ROS) [138] Recently, antioxidant conjugation has been used to remedy this problem [139] The study of complex cytological effects of materials is also urgently needed. For example, cell damage and apoptosis caused by PEG-coated GNPs can be inhibited by antibodies formed after peptide functionalization [140].…”
Section: Challengesmentioning
confidence: 99%